A rapid realist review of literature examining Co‐production in mental health services for youth - Verity Rose Jones; Justin Waring; Nicola Wright; Sarah‐Jane Fenton (JCPP Advances)
Abstract Background An overview of internationally published literature on what works for co‐production in youth mental health services is missing, despite a practice and policy context strongly recommending this approach. This rapid realist review develops a theory about how and why co‐production methods in youth mental health services work, for whom and in which circumstances. Methods Relevant evidence was synthesised to develop Context–Mechanism–Outcome configurations (CMOs) that can inform policy and practice. Stakeholders were iteratively involved by engaging an expert panel including young people and a separate youth advisory group. Searches across eight databases and expert panel suggestions identified 5716 documents which were screened at abstract level, 532 at full‐text and 57 documents were included in the review. Results Data extracted from 57 papers contributed to five CMO configurations to describe the generative mechanisms by which co‐production in youth mental health services are linked to outcomes and influenced by context. The final programme theory is: Youth experts by experience (YEBE), particularly those from minoritised communities, provided with a supportive organisational culture can experience authentic engagement where their knowledge is perceived as credible by wider stakeholders. This leads to personal development for participating YEBE as well as service improvements from their input. Conclusions Rich data from a heterogenous sample of papers along with stakeholder consultation enabled this review to refine a clear programme theory for co‐production in mental health services for young people. Nevertheless, further information is needed to identify what constitutes a supportive organisational culture and to explore rival theories or under‐evidenced areas.